2019
DOI: 10.1111/bjd.18638
|View full text |Cite
|
Sign up to set email alerts
|

Topically applied treatments for external genital warts in nonimmunocompromised patients: a systematic review and network meta‐analysis

Abstract: trichloroacetic acid (TCA) with podophyllin, and unconventional or newly emerging modalities, such as cidofovir gel, idoxuridine, polyhexamethylene biguanide, sodium nitrite with citric acid, and SB206 12%. The lack of head-to-head comparative analysis of various therapies renders choice of treatment a clinical challenge. Therefore, we performed a network meta-analysis (NMA) that provided direct, indirect and mixed evidence 13 to compare multiple treatments simultaneously regarding their efficacy and safety. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 53 publications
(221 reference statements)
0
9
1
Order By: Relevance
“…Only two cases reported the onset of a slight erythema without edema after 60 days of therapy, without however determining the interruption of the treatment. This level of tolerability is certainly higher than that reported in a recent meta-analysis (27), where many of the topical drugs used determined severe adverse events that led to patient withdrawal: the analysis of 17 studies showed that imiquimod 5% cream (OR: 8.68; 95% CI: 1.01-74.43), podophyllin 2.0% solution (OR: 38.43; 95% CI: 1.28-1156.07), podophyllotoxin 0.5% cream (OR: 5.98; 95% CI: 1.07-33.54), polyhexamethylene biguanide cream (OR: 55.87; 95% CI: 3.33-937.61) and sinecatechins 10% (OR: 8.03; 95% CI: 3.97-16.24) and 15% cream (OR: 8.54; 95% CI: 4.23-17.25) were associated with significantly higher numbers of patients with severe adverse events or patients who were lost to follow-up because of treatment-related side effects, compared to the placebo; Imiquimod 5% cream can determine the development of severe erythema and erosions even in the 40% of cases, podophyllin 2.0%, polyhexamethylene biguanide cream, and sinatechins seems to determine severe local reaction or severe erythema in 4, 22 and 28% of cases, respectively. The analysis of the rate of persistence or regression of GW after 60 days of therapy showed a significant decrease in the median number of GW and of quadrants involved and a complete response to therapy in 61.6% of patients that, therefore, they avoided a destructive therapy.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Only two cases reported the onset of a slight erythema without edema after 60 days of therapy, without however determining the interruption of the treatment. This level of tolerability is certainly higher than that reported in a recent meta-analysis (27), where many of the topical drugs used determined severe adverse events that led to patient withdrawal: the analysis of 17 studies showed that imiquimod 5% cream (OR: 8.68; 95% CI: 1.01-74.43), podophyllin 2.0% solution (OR: 38.43; 95% CI: 1.28-1156.07), podophyllotoxin 0.5% cream (OR: 5.98; 95% CI: 1.07-33.54), polyhexamethylene biguanide cream (OR: 55.87; 95% CI: 3.33-937.61) and sinecatechins 10% (OR: 8.03; 95% CI: 3.97-16.24) and 15% cream (OR: 8.54; 95% CI: 4.23-17.25) were associated with significantly higher numbers of patients with severe adverse events or patients who were lost to follow-up because of treatment-related side effects, compared to the placebo; Imiquimod 5% cream can determine the development of severe erythema and erosions even in the 40% of cases, podophyllin 2.0%, polyhexamethylene biguanide cream, and sinatechins seems to determine severe local reaction or severe erythema in 4, 22 and 28% of cases, respectively. The analysis of the rate of persistence or regression of GW after 60 days of therapy showed a significant decrease in the median number of GW and of quadrants involved and a complete response to therapy in 61.6% of patients that, therefore, they avoided a destructive therapy.…”
Section: Discussioncontrasting
confidence: 58%
“…The analysis of the rate of persistence or regression of GW after 60 days of therapy showed a significant decrease in the median number of GW and of quadrants involved and a complete response to therapy in 61.6% of patients that, therefore, they avoided a destructive therapy. This data is not comparable with other topical preparations for GW (27) because there is not a cohort treated with placebo and because, despite the number of our treated patients with P. acnes preparations is considerable, it would be necessary an efficacy studies or a RCT to evaluate their outcomes. When compared to placebo (25), all other treatments were significantly more efficacious: Podophyllotoxin 0.5% solution was significantly superior to imiquimod 5% cream for lesion clearance, although it was associated with a higher overall rate of adverse events.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Treatments are either ablative (excision, resection, vaporization, coagulation, or laser therapy), minimally ablative (Podophyline, keratolytics, caustics, cryotherapy, or immunomodulators), injection immunotherapy, or HPV vaccines. Most of the treatments used can cause hyper or hypo-pigmentaion, irritation, pain and permanent scarring [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the BJD , Jung et al . review topically applied treatments for external genital warts in nonimmunocompromised patients.…”
mentioning
confidence: 99%